A Multimodal Degree Completion Needs Analysis of Agricultural and Extension Education Graduate Students in Sub-Saharan Africa - Millicent A Oyugi; Mathew Baker; Alexa Lamm; Kevan W Lamm (Journal of International Agricultural and Extension Education, 2022)
Increasing doctoral degree holders in Sub-Saharan Africa may significantly impact the quality and quantity of undergraduate and graduate programs. Research capacity is crucial to successfully completing a thesis or dissertation and obtaining a graduate degree. Unfortunately, in Sub-Saharan Africa, many students abandon or delay their degrees at this stage due to limited research and writing skills. This study aimed to identify the most critical thesis and dissertation (TD) research needs of masters and PhD students from Sub-Saharan Africa. Thirty-eight skills were identified from the literature and presented to agricultural education and extension/leadership students. Borich (1980) and Witkin (1984) needs assessment models were used to ascertain the perceived importance and extent of students' knowledge of TD topic areas. The top identified needs were extracting a manuscript from a thesis, writing a journal article, choosing inferential statistics, deciding the descriptive statics, and what to review in the literature. A total of 15 items were identified as critical needs using the Witkin model. The findings identified challenges and opportunities for improving Sub-Saharan African graduate students' research knowledge and TD performance, implying that combining the two models to identify training needs may produce more comprehensive results than using only one methodology.
Keywords: Witkin; Borich; research needs; graduate degree completion; Sub-Saharan Africa